Law and risk (Legal dimensions series ;, 2005)
"This book looks at law and risk in a variety of contexts and provides insight into how courts use and interpret risk and how the law allocates risk, as well as examining the regulation of risky activities. To demonstrate the linkages between law and risk, the essays tackle some difficult topics, including dangerous offenders, sex offender notification, drug courts, genetic research, pesticide use, child pornography, and tobacco advertising."--Jacket